SILKY STRAWBERRY MILK: A NUTRITIOUS DAIRY INNOVATION FOR STUNTING PREVENTION - Prodyanatasari, Arshy; Purnadianti, Mely (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2025)
Introduction: Stunting, characterized by impaired child growth, results from multiple factors including inadequate nutrition. Fresh cow's milk, rich in essential nutrients, offers a viable solution. Currently, fresh cow's milk products are deposited to BUMDES with a relatively low purchase price and limited consumer market reach. Currently, fresh milk is only stored and sold through the village-owned enterprise (BUMDES), but demand is low due to its smell and taste, as well as the lack of public awareness about the benefits of fresh milk. Therefore, a high-nutrient processed fresh milk product has been developed as an alternative dessert to support the prevention of stunting in children. Methods: Counseling was conducted on the benefits, processing, and proper storage of fresh milk, as well as a demonstration of making Silky Strawberry Milk. The methods used were lectures and a hands-on demonstration of Silky Strawberry Milk production. The activity was carried out on March 16, 2024, at the Blimbing Village, Kediri Regency. It was attended by 28 participants. Pretest-posttest evaluations confirmed significant improvement in participants' knowledge regarding milk nutrition and processing methods. Results: Silky Strawberry Milk was distributed to participants. They loved its delicious taste, fresh aroma, and attractive colour. This product is expected to increase milk consumption to prevent stunting through better nutrition. Conclusion: Silky Strawberry Milk has been well received by the public due to its delicious taste and attractive appearance. This product has the potential to increase milk consumption and prevent stunting through improved child nutrition.